2014
DOI: 10.1111/bph.12789
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological manipulations in animal models of anorexia and binge eating in relation to humans

Abstract: Eating disorders, such as anorexia nervosa (AN), bulimia nervosa (BN) and binge eating disorders (BED), are described as abnormal eating habits that usually involve insufficient or excessive food intake. Animal models have been developed that provide insight into certain aspects of eating disorders. Several drugs have been found efficacious in these animal models and some of them have eventually proven useful in the treatment of eating disorders. This review will cover the role of monoaminergic neurotransmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 222 publications
(251 reference statements)
1
16
0
Order By: Relevance
“…Given that dysfunctions of brain DA system are implicated in the development of binge eating in humans (18, 19), we speculated that 5-HT 2C Rs expressed by DA neurons may be involved in the inhibitory effects of 5-HT drugs on binge-like eating. To test this possibility, we first used TPH2-CreER mice which express tamoxifen-inducible Cre recombinase exclusively in TPH2-expressing neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that dysfunctions of brain DA system are implicated in the development of binge eating in humans (18, 19), we speculated that 5-HT 2C Rs expressed by DA neurons may be involved in the inhibitory effects of 5-HT drugs on binge-like eating. To test this possibility, we first used TPH2-CreER mice which express tamoxifen-inducible Cre recombinase exclusively in TPH2-expressing neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The central dopamine (DA) system is also implicated in the pathophysiology of binge eating (18). For instance, human genetic studies have shown an increased frequency of DA transporter (DAT) and D2 receptor polymorphisms with binge pathology (19).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of animal models have been developed in order to characterise the possible mechanisms involved in pathological eating behaviour and weight homeostasis in humans [17][18][19][20]. These models are based upon findings from lesion studies, pharmacological manipulations and by controlling the environmental conditions of rodents.…”
Section: Animal Models Of Eating Behaviour-possible Translational Insmentioning
confidence: 99%
“…This model involves using a gastric fistula to induce drainage of consumed food before it enters the intestine [20]. Under such states, rats show an increase in binge eating behaviour as compared to control rats [46].…”
Section: Rodent Models Of Non-homeostatic 'Binge-like' Eatingmentioning
confidence: 99%
“…Aberrant eating patterns are increasingly likened to addiction disorders due to common psychological and anatomical systems being implicated in both disorders. There are a number of models that recapitulate facets of both binge eating and anorexia nervosa (van Gestel et al ., ). In both cases, drugs targeting monoamine systems are a major focus of preclinical and clinical investigations.…”
mentioning
confidence: 97%